Evaluasi Kesuksesan Sistem Informasi Manajemen Rumah Sakit dengan Metode Delone and Mclean - Mochammad Arief Darmawan; Dony Setiawan Hendyca Putra (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
SIMRS at RSIA Srikandi IBI Jember has been running since 2011. However, based on the preliminary studyfound several problems including, there are some data that is not stored properly, information generated bySIMRS is still incomplete or incomplete, and the discovery of several system users who are not satisfied withthe SIMRS. Therefore, it is necessary to further study how to evaluate the success of the implementation ofthe SIMRS by using the Update D&M IS Success Model evaluation method (Delone and Mclean 2003). Thepurpose of this study is to evaluate the performance of SIMRS in supporting service activities based onvariables of system quality, information quality, service quality, intensity of use, usage, user satisfaction andnet benefits. The analysis used is the analysis of the relationship with the Spearman rank test using the SPSS24.0 program. The results of this study indicate the significance value of all variables <0.05 and positive value,so that the quality of the system, the quality of information, the quality of service is related to the direction ofthe intensity of use and user satisfaction. Usage intensity and user satisfaction are also related to the directionof net benefits. A very strong influence occurs on service quality on the intensity of use with a significancevalue of 0,000 and a coefficient correlation value of 0.826. The influence that is going on on the quality ofinformation on user satisfaction with a significance value of 0,000 and a coefficient correlation value of 0.425.